KONTRIBUSI KEKUATAN OTOT LENGAN DAN KOORDINASI MATA-TANGAN TERHADAP KEMAMPUAN SERVIS ATAS BOLA VOLI SISWA SMA NEGERI 1 KOTABARU - Ishak Bachtiar; Faisal Batennie (STKIP Paris Barantai, 2022)
English translation. This study aims to determine the contribution of arm muscle strength to the service ability of SMA Negeri 1 Kotabaru volleyball. To find out the contribution of eye-hand coordination to the ability of service over volleyball. To find out the contribution of arm muscle strength and eye-hand coordination to the ability to serve volleyball. The population is the Overall Students of SMA Negeri 1 Kotabaru. Sampling was carried out randomly with a total sample of 35 people. The data analysis technique used is by the method of multiple regression with the SPSS 25.0 for windows program. The results showed that there was a significant contribution between the strength of the arm muscles to the serviceability of volleyball students of Kotabaru State High School, amounting to 28.5%. There was a significant contribution between hand-eye coordination to the ability to serve volleyball by 25.7%. There was a significant contribution between arm muscle strength and eye-hand coordination to volleyball top service ability of 43.5% with an F value: 12.297 and a sig (p)= 0.000. Keywords: Balance, Eye-hand coordination and top service